Comprehensive assessment on the viability for establishing waste cooking oil (WCO) biodiesel processing facility in an eco-tourism island - Razali N.M.; Abdullah T.A.R.T.; Ibrahim W.A.; Nassri M.N.M. (Zibeline International Publishing Sdn. Bhd., 2023)
The successful implementation of biodiesel derived from waste cooking oil (WCO) is highly dependent on the waste management mechanism to ensure sustainable feedstock volume and price. In eco-tourism island of Langkawi Kedah Malaysia, a comprehensive assessment has been conducted to gather hard data on the recoverable WCO quantity from daily cooking oil utilization around the island. Based on this primary information, the rate of WCO recoverability and its volume projection has been further assessed to anticipate viability for establishing a full-pledged WCO biodiesel processing plant facility to support its local diesel market demand. The findings concluded that presently, only a WCO management facility is viable for implementation in the island with essential key enablers being made available by key stakeholder. 2019 Journal of Global Pharma Technology. All rights reserved.